2019
DOI: 10.3390/diseases7020046
|View full text |Cite
|
Sign up to set email alerts
|

Preoperatory Anxiety in Patients Undergoing Cardiac Surgery

Abstract: Anxiety is a feeling of discomfort produced in face of an unknown event, as an impending cardiac surgery, that can lead to inconveniences in the intervention and subsequent recovery. Being the purpose of this research to analyze pre-surgical anxiety, a descriptive cross-sectional study among patients undergoing cardiac surgery was carried out. Data about sociodemographic variables were collected and the level of anxiety prior to surgery was assessed using the STAI-S scale. Subsequently, descriptive data analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 21 publications
(42 reference statements)
1
29
0
4
Order By: Relevance
“…The preoperative anxiety among surgical patients is not routinely performed as part of preoperative patient evaluation and preparation for Anesthesia and surgery (5,(74)(75)(76)(77). However, body of evidences revealed that preoperative anxiety contributed a huge impact on perioperative undesirable outcomes including increased doses of induction agents (11,22,78,79), hemodynamic instability (11,22,27,52,79), cardiac morbidity and mortality in high risk patients (26,51,64,80,81), postoperative pain and increased consumption of analgesics (18,72,74,78,(82)(83)(84)(85)(86), postoperative delirium(87), patient dissatisfaction (88)(89)(90)(91), increased hospital length of stay (29,89,92) and these in turn can incur a signi cant health care cost (1,86,89,92).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The preoperative anxiety among surgical patients is not routinely performed as part of preoperative patient evaluation and preparation for Anesthesia and surgery (5,(74)(75)(76)(77). However, body of evidences revealed that preoperative anxiety contributed a huge impact on perioperative undesirable outcomes including increased doses of induction agents (11,22,78,79), hemodynamic instability (11,22,27,52,79), cardiac morbidity and mortality in high risk patients (26,51,64,80,81), postoperative pain and increased consumption of analgesics (18,72,74,78,(82)(83)(84)(85)(86), postoperative delirium(87), patient dissatisfaction (88)(89)(90)(91), increased hospital length of stay (29,89,92) and these in turn can incur a signi cant health care cost (1,86,89,92).…”
Section: Discussionmentioning
confidence: 99%
“…The Meta-Analysis revealed that the prevalence of preoperative anxiety was the highest in the obstetric patient(27) followed by other major surgical (11,16,21,30,35,36,38,67,69) and cardiac surgery patients (7,26) while the lowest was seen in cancer patients (25,32,(71)(72)(73). These variations can be explained by two lives in the obstetric patient, a small number of included studies, and inclusion of heterogeneous groups in studies with all surgical patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Según estos estudios, la incidencia se considera baja y no prolonga la estancia en la UC, por lo que no se considera necesario la administración de fármacos antieméticos como profilaxis en pacientes sin factores de riesgo [163][164][165] . 62. En pacientes sin factores de riesgo, siempre que haya un plan de rescate eficaz, se sugiere no realizar profilaxis sistemática de NVPO.…”
Section: Prevención De Náuseas Y Vómitos Postoperatoriosunclassified
“…Prado-Olivares and Chover-Sierra [1] reported that the level of preoperatory anxiety in patients undergoing cardiac surgery is significantly associated with level of studies, first surgical intervention, and the rating given to their previous surgical experience. The relationship between the received information and the anxiety level is inversely correlated, so these patients should be provided with all the information through an individualized intervention to reduce their anxiety and its related adverse outcomes.…”
mentioning
confidence: 99%